Structural, optical and photocatalytic properties of flower-like ZnO nanostructures prepared by a facile wet chemical method - Kuriakose, Sini; Bhardwaj, Neha; Singh, Jaspal; Satpati, Biswarup; Mohapatra, Satyabrata (Beilstein Journal of Nanotechnology, 2013)
Flower-like ZnO nanostructures were synthesized by a facile wet chemical method. Structural, optical and photocatalytic properties of these nanostructures have been studied by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), photoluminescence (PL) and UV–vis absorption spectroscopy. SEM and TEM studies revealed flower-like structures consisting of nanosheets, formed due to oriented attachment of ZnO nanoparticles. Flower-like ZnO structures showed enhanced photocatalytic activity towards sun-light driven photodegradation of methylene blue dye (MB) as compared to ZnO nanoparticles. XRD, UV–vis absorption, PL, FTIR and TEM studies revealed the formation of Zn(OH)2 surface layer on ZnO nanostructures upon ageing. We demonstrate that the formation of a passivating Zn(OH)2 surface layer on the ZnO nanostructures upon ageing deteriorates their efficiency to photocatalytically degrade of MB.
Keywords: ageing; nanoparticles; nanosheets; photocatalysis; ZnO